Cristalização e sinterização de bio vidros do sistema Na2O-CaO-SiO2-P2O5 - Leite, Magda Lauri Gomes (2001)
The objective of this work was to study crystallisation and sintering of Bio-glasses of Na2O CaO SiO2 P2O5 aiming at the improvement of the mechanical properties. In order to study the development of glass-ceramics in this system, the effects of the addition of different percentages of NaF, Fe2O3, Li2O, ZrO2, TiO2 and WO3 on the behaviour of crystallisation of the glasses were studied using DSC. The results show that amongst the additions that were tested only Li2O caused increased volumetric nucleation rate. Different melting techniques were tested to obtain glasses with different concentrations of OH-. Although glasses with different contents were obtained successfully, there were problems to homogenise them. The direct extrusion technique was used to produce glass-ceramics with texture. Albeit the technique was efficient with several other systems, the results obtained in the present word showed that the glass-ceramic produced from the extruded glasses did not have the same symmetry that was showed by the glasses that were not extruded. The difficulties in sintering, related to the process of crystallisation, were analysed for two compositions of bio-glasses. Two new crystalline phases, which had not yet been observed in this system, were identified in the studies of sintering. Experimental data showed that superficial crystallisation has strong influence during the process of sintering for both glasses tested. It was not possible to obtain sintered bodies with relative density superior to 0.94 for the experimental conditions that were used. The use of the model that simulates the sintering of the glass proved to be useful to simulate the real effect of each parameter in the process, although it overestimated the ability of sintering of the compositions that were used. The use of this model can facilitate the process of searching solutions for a more efficient sintering process. Using the technique of FTIR, the studies of bioactivity of both glass and glass-ceramic powders revelled higher level of bioactivity for finer powders, and which contained phosphorus in their compositions. It was also verified that whilst total crystallisation hinders the formation of the layer of HCA, partial crystallisation seems to have beneficial effect in the process.